Building Performance Analysis and Optimization: A Study on Energy Efficiency and Sustainability - Nijah Akram; Dr. Nosheen Blouch; Dr. Ayesha Mehmood Malik; Fatima Sher; Roma Mukhtar; Wasim Rafi Khan (Social Science Review Archives, 2025)
This study focused on performance analysis, optimization, energy efficiency, and sustainability within the context of Pakistan. It outlined the developments and challenges of energy consumption within the residential and commercial sectors of the major cities of Pakistan during the early phase of urban expansion, additional population growth, and their resultant challenges on sustainable development. Within this context, the researchers utilized a mixed-methods approach, combining qualitative energy audits of different buildings with qualitative assessments of construction practices and building code implementation. Data were obtained by thermal imaging, utility consumption analysis, and interviews with building design stakeholders (architects, engineers, building occupants). Research findings indicated a decline in energy efficiency within the buildings of Pakistan, as a result of poor insulation, inefficient AND unregulated HVAC, fenestration design, and a general lack of passive cooling in buildings. Considering the context of the climate, the research found buildings were consuming 40-50% energy on top of the international standards set for buildings of the same climate zone. Considering these findings, the research presented optimization with retrofitting focused on cost, socio-economic conditions of Pakistan, sustainable local materials, passive design, and the Pakistan climate. As highlighted in the results, the recommendations can still keep the thermal comfort standards while reducing building energy usage by 25-35%. This will be a step towards reaching the energy security and environmental sustainability targets of Pakistan.